Comparative Evaluation of Lercanidipine and Amlodipine in Hypertensive Patients: Efficacy, Tolerability, and the Role of Gut Microbiota Modulation - Aziz, Nighat; Bano, Rahila; Mehar, Uzma Jabeen; Khan Malik, Muhammad; Khan, Obid Ullah; Basir, Noor ul (Journal of Neonatal Surgery, 2025)
Background: Hypertension affects over 1.28 billion adults globally and is a major contributor to cardiovascular morbidity and mortality. Calcium channel blockers, such as lercanidipine and amlodipine, are widely prescribed for hypertension management, yet their differential impact on gut microbiota remains underexplored. Objective: This study aimed to compare the efficacy, tolerability, and microbiota-modulating effects of lercanidipine versus amlodipine in hypertensive patients over a 12-month period. Methods: A randomized, open-label clinical trial was conducted at three tertiary care hospitals in Peshawar, Pakistan, involving 320 adults with essential hypertension. Participants were randomly assigned to receive either lercanidipine 10 mg or amlodipine 5 mg once daily. Blood pressure was monitored monthly, and treatment adherence, adverse effects, and gut microbiota changes were assessed. Stool samples were collected at baseline and after 12 months for 16S rRNA sequencing. Statistical comparisons were made using t-tests, ANOVA, and Kaplan–Meier survival analysis. Results: Both groups exhibited significant reductions in systolic and diastolic blood pressure, with lercanidipine achieving target levels faster (4.2 vs. 5.6 weeks). Lercanidipine was associated with higher adherence (92% vs. 85%) and fewer cases of peripheral edema (5% vs. 12%). Gut microbiota analysis revealed that lercanidipine preserved alpha diversity and enriched beneficial genera such as Faecalibacterium and Lactobacillus, whereas amlodipine led to decreased diversity and an increase in Escherichia/Shigella abundance. Conclusion: Both drugs work well to lower blood pressure, yet lercanidipine has a better chance of tolerance, quicker action on blood pressure and helps improve gut bacteria. These findings suggest its potential as a preferable choice in personalized hypertension management, participating microbial health consideration.